Bike allocation strategies in a competitive dockless bike sharing market. (1st October 2019) - Zhang, J.; Meng, M.
Abstract: This paper investigates bike allocation strategy in a competitive dockless bike sharing market from both market leader and market follower's perspective. Market leader aims to grasp the market using the shortest time, while market follower wants to get the market share from market leader. The initial bike allocation position, coverage area and allocation method are investigated based on community structure method. An approximate optimal allocation model is proposed to maximise the recourses. Numerical examples are tested in a simplified Sioux Falls network and a real bike sharing network in Singapore to illustrate the effectiveness and practicability. Results show that the proposed method could identify the reasonable and efficient allocation position quickly. Market follower should apply the same allocation strategy as market leader, while use lower ticket, more bikes, and large batches allocation to strive for market share.